(untitled) (Journal of the Bangladesh Agricultural University, 2025)
A fracture refers to the occurrence of a break or interruption in the bone. The prevalence of long bone fractures in cats is on the rise due to the expanding population of domestic felines. The femur accounts for approximately 50.82% of long bone fractures, followed by the tibia-fibula at 29.05%, the radius-ulna at 10.61%, and the humerus at 9.5%. Motor vehicle accidents are the majority of fracture causes, accounting for 42.55% of cases. In contrast, dog biting, falls, and other accidents contribute to 12.76%, 4.25%, and 6.38% of fractures, correspondingly. Numerous treatments exist for managing fractures, including cerclage and Kirschner (K) wires, external skeletal fixation (ESF), bone plates, intramedullary pins, interlocking nail implantation, and the utilization of a combination bone plate-intramedullary pin construct, etc. The bone plating system is a modern and efficient method of internal fixing. There are many plating technologies that may be utilized for the purpose of correcting long bone fractures in felines such as dynamic compression plates (DCP), limited contact dynamic compression plate (LC-DCP), veterinary cuttable plates (VCP), locking plates, etc. In comparison to alternative fixation procedures, bone plates exhibit a superior recovery rate and a reduced incidence of post-operative complications. This study aims to exhibit different types of bone plates for the efficient execution of bone plating surgery and examine the effectiveness of bone plating systems in the treatment of long bone fractures in felines. J Bangladesh Agril Univ 23(3): 377–385, 2025